Relative expression of proinflammatory cytokines by real time PCR in milk somatic cells of subclinical mastitis affected buffaloes - SINGH, MAHAVIR; SHARMA, ANSHU; KUMAR, AMAN; MITTAL, DINESH; KUMAR, PAWAN; CHARAYA, GAURAV (The Indian Journal of Animal Sciences, 2016)
The expression profile of proinflammatory cytokines including TNFa, IL1b, IL6 and IFNg were investigated in milk somatic cells of subclinical mastitis affected buffaloes using real time PCR assay. Relative expression levels of target mRNAs were analysed by comparison with the expression of the housekeeping gene, b-actin within each animal. Highest relative transcript level of TNFa (44.93 ± 1.16) was observed followed by IL1b (19.92 ± 1.78), IL6 (4.72 ± 1.96) and IFNg (2.55 ± 2.23) from milk somatic cells of subclinical mastitis with respect to healthy ones. Lowest upregulation of IFN-g in the present study attributed to the isolation of only Gram positive bacteria (staphylococci and streptococci) from subclinical mastitis cases. Monitoring of cytokines involved in the regulation of immune responses during the infection is useful in determining cytokine markers that could be utilized as a forecasting tool in the early diagnosis of subclinical mastitis.